2011
DOI: 10.1146/annurev-anthro-081309-145711
|View full text |Cite
|
Sign up to set email alerts
|

The Human Microbiota as a Marker for Migrations of Individuals and Populations

Abstract: In this review, we discuss evidence that the microbes that constitute the human microbiota coevolved with humans and maintain complex community and host interactions. Because these microbes are mostly vertically transmitted, they have evolved within each human group and provide a view of human ancestry. In particular, we discuss using Helicobacter pylori as a marker of ancestry and migrations. Other organisms with more mixed vertical and horizontal transmission are not suitable to trace migrations with any fid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 212 publications
0
33
0
1
Order By: Relevance
“…Geographic distance can be positively correlated with microbiota dissimilarity (Dominguez-Bello & Blaser, 2011), but local flora and fauna, photoperiod, available food, climate conditions, etc. may all affect microbiota and differ by locality.…”
Section: Discussionmentioning
confidence: 99%
“…Geographic distance can be positively correlated with microbiota dissimilarity (Dominguez-Bello & Blaser, 2011), but local flora and fauna, photoperiod, available food, climate conditions, etc. may all affect microbiota and differ by locality.…”
Section: Discussionmentioning
confidence: 99%
“…As a result of these characteristics, Helicobacter pylori has long been a prime candidate to determine past migrations (5863), possible admixture (64) and genetic ancestry (65, 66) of current and ancient cultures. For instance, genetic admixture and past migrations are evident with the widespread presence of European H. pylori strains in North and South America, which are possibly remnants of massive colonial expansions, while in comparison rural Amerindian communities commonly harbor strains of Asian origins, products of pre-Columbian migrations to the New World (6769).…”
Section: Potential Pathogens or Ancient Symbionts?mentioning
confidence: 99%
“…Several of these pathobionts have been identified in ancient dental calculus [104], and further research may yield insights into the evolution of their pathogenicity [105]. Studies of pathobionts can also reveal information about past human migration events [155, 156]. A recent study of H. pylori recovered from the stomach tissue of the Tyrolean Iceman found that Asian strains predate African strains within Europe, indicating that the hybrid population of H. pylori found in Europe today is a recent development [125].…”
Section: Ancient Microbiome Researchmentioning
confidence: 99%
“…( n ) Gut microbes synthesize B and K vitamins [82, 83], catabolize xenobiotics, drugs, and toxins [65], and play key roles in cholesterol and bile acid metabolism [84]. ( o ) Some microbial strains exhibit patterns of genetic variation that mirror human migration histories [125, 155, 156]. …”
Section: Figurementioning
confidence: 99%